IMPLEMENTASI ALGORITMA DIJKSTRA UNTUK MENCARI RUTE TERPENDEK ANTAR KANTOR DAN ESTIMASI BIAYA PENGGUNAAN BBM (STUDI KASUS PT.TELKOM INDONESIA REGIONAL IV JATENG-DIY) - Eka Andiany, Fairuz; Hadikurniawati, Wiwien (Information Technology and Telematics, 2018)
ABSTRACT Employees get adequate facilities to support working. PT Telkom Indonesia provides car loan facilities for employee mobility. For employees with divisions whose work has high mobility, cars and costs needed to facilitate going to the destination. Borrowing the car with a predetermined procedure. Web was chosen as a means to borrow cars. The web that is created not only requires regular web, but also comes with an algorithm to find costs of petrol. The algorithm that is used is Dijkstra's algorithm. Based on literature study, Dijkstra's algorithm is able to determine the shortest route for a predetermined purpose.